Infections with the tick-borne bacterium "Candidatus Neoehrlichia mikurensis" mimic noninfectious conditions in patients with B cell malignancies or autoimmune diseases - Grankvist, Anna; Andersson, Per-Ola; Mattsson, Mattias; Sender, Monica; Vaht, Krista; Höper, Linnea; Sakiniene, Egidija; Trysberg, Estelle; Stenson, Martin; Fehr, Jan; Pekova, Sona; Bogdan, Christian; et al. (Clinical infectious diseases, 2014)
BACKGROUND: Candidatus Neoehrlichia mikurensis is a newly discovered noncultivatable bacterium spread among ticks and rodents in Europe and Asia that can infect humans, particularly immunocompromised patients. METHODS: We compiled clinical and laboratory data from 11 patients with hematological malignances or autoimmune diseases who were diagnosed with Candidatus N. mikurensis infection in Europe 2010-2013. Both published (6) and unpublished cases (5) were included. RESULTS: The patients had a median age of 67, were mostly male (8/11), and resided in Sweden, Switzerland, Germany, and the Czech Republic. All but one had ongoing or recent immune suppressive treatment and a majority were splenectomized (8/11). Less than half of them recalled tick exposure. The most frequent symptoms were fever (11/11), localized pain afflicting muscles and/or joints (8/11), vascular and thromboembolic events (6/11), that is, deep vein thrombosis (4), transitory ischemic attacks (2), pulmonary embolism (1), and arterial aneurysm (1). Typical laboratory findings were elevated C-reactive protein, leukocytosis with neutrophilia, and anemia. Median time from onset of symptoms to correct diagnosis was 2 months. In at least 4 cases, the condition was interpreted to be due to the underlying disease, and immunosuppressive therapy was scheduled. All patients recovered completely when doxycycline was administered. CONCLUSIONS: Candidatus N. mikurensis is an emerging tick-borne pathogen that may give rise to a systemic inflammatory syndrome in persons with hematologic or autoimmune diseases that could be mistaken for recurrence of the underlying disease and/or unrelated arteriosclerotic vascular events. Awareness of this new pathogen is warranted among rheumatologists, hematologists, oncologists, and infectious disease specialists.
Keywords: autoimunitní nemoci; senioři; Delayed Diagnosis; C-Reactive Protein; Pulmonary Embolism; Anti-Bacterial Agents; B-cell malignancies; DNA, Bacterial; hematologické nádory; opožděná diagnóza; Communicable Diseases, Emerging; plicní embolie; C-reaktivní protein; Middle Aged; Hematologic Neoplasms; aneurysma; mužské pohlaví; infekce bakteriemi čeledi Anaplasmataceae; human; Autoimmune Diseases; objevující se infekční nemoci; Anaplasmataceae Infections; DNA bakterií; Ischemic Attack, Transient; žilní trombóza; muskuloskeletální bolest; ženské pohlaví; Humans; horečka; Aneurysm; Musculoskeletal Pain; antibakteriální látky; lidé středního věku; Fever; splenektomie; infection, Neoehrlichia; tick-borne; nemoci přenášené klíšťaty; Splenectomy; Tick-Borne Diseases; tranzitorní ischemická ataka; Female; Aged; Venous Thrombosis; lidé; Male